Balance and Isokinetic Strength of Lower Limb Muscles in Professional Female Volleyball Players with Patellofemoral Pain Syndrome - Khodarahmi, Sara; Fatahi, Ali; Sokhanguei , Yahya (Journal of Clinical Physiotherapy Research, 2022)
Introduction: Patellofemoral pain syndrome (PFPS) is one of the prevalent musculoskeletal disorders of the knee, which subsequently causes joint changes in the knee. Investigating balance and muscle strength should be considered in the evaluation of these people. The present study aimed to compare balance and lower limb muscle strength in female volleyball players with PFPS and their healthy peers. Materials and Methods: In this cross-sectional study, 30 people (14 people with PFPS and 16 healthy peers) with mean±sd age of 24.33±3.12 years, height 178.72±0.06 cm, and Body Mass 67.76± 6.95 kg participated in this research. Biodex balance system was used to assess the balance as center of pressure (COP) displacement for anterior-posterior and medial-lateral directions in two open and closed-eye conditions. The evaluation of isokinetic strength of ankle, knee extensor, and hip abductor-external rotator muscles as peak torques and (PT) time-to-peak torque (TTPT) was measured by Cybex isokinetic dynamometer at a speed of 60 deg./s. The data were analyzed using MANOVA to compare two healthy and PFPS groups in SPSS software ver. 26 (P<0.05). Results: findings showed that the static balance in all tests conditions of female with PFPS was significantly decreased in compared to healthy ones (P<0.05). The strength of all evaluated muscles, except for the plantar flexor muscle group, was significantly lower in females with PFPS compared with healthy ones (P<0.05). Conclusion: The results demonstrated that static balance and muscle strength of lower limb in individuals with PFPS are weaker than in healthy ones, which can cause more injuries. Therefore, it is suggested that in the treatment and rehabilitation of this injury, strengthening the muscle and balance should also be considered for these people.